A study of China's uranium resources security issues: Based on analysis of China's nuclear power development trend. (December 2017) - Xing, Wanli; Wang, Anjian; Yan, Qiang; Chen, Shan
Highlights: By 2030, the demand of china's uranium resources will be 20113tU. China's uranium production increases slowly, making external dependency rise. There are potential supply risks because the source of China's imports is concentrated. Global uranium resources tend to be controlled by a monopoly. With the development of nuclear power industries in developing countries, uranium prices will go higher. Abstract: It is difficult for China to use its domestic uranium resources to meet its demand, so its external dependency will remain at a high level, which is not conducive to the sustainable development of the nuclear power industry in China. This paper analyzes the supply and demand pattern of uranium resources in the world, and forecasts the demand for uranium resources in China to 2030. According to our empirical model, together with China's nuclear power development plan, demand will reach 20113 tU by 2030 (in the medium scenario). In addition, we discuss four problems associated with China's uranium resources: (1) domestic uranium production is increasing slowly, so the country's external dependency is rising; (2) there are potential supply risks because the source of imports is concentrated; (3) global uranium resources tend to be controlled by a monopoly, so there is the possibility of manipulating the market; and (4) with the development of a nuclear power industry in developing countries, uranium prices will rise significantly. Finally, we offer relevant countermeasures and suggestions.